2010
DOI: 10.1099/jmm.0.013201-0
|View full text |Cite
|
Sign up to set email alerts
|

Molecular emm genotyping and antibiotic susceptibility of Streptococcus dysgalactiae subsp. equisimilis isolated from invasive and non-invasive infections

Abstract: To analyse the characteristics of infections caused by Streptococcus dysgalactiae subsp. equisimilis, clinical isolates (n5145) were collected at 11 medical institutions between September 2003 and October 2005. These isolates belonged to Lancefield group A (n55), group C (n518) or group G (n5122). Among all isolates, 42 strains were isolated from sterile samples such as blood, synovial fluid and tissue specimens from patients who were mostly over 50 years with invasive infections, and included seven cases of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
40
6
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 35 publications
5
40
6
2
Order By: Relevance
“…equisimilis (SDSE) has increasingly been recognized as the aetiological agent of several human invasive infections worldwide (Bruun et al, 2013;Sunaoshi et al, 2010;Takahashi et al, 2010Takahashi et al, , 2011Tsai et al, 2014). SDSE isolates are frequently classified as Lancefield group C or G. Comparative genomic analyses revealed that several commonly found group A streptococci virulence factors have also been detected in SDSE isolates, including C5a peptidase, M protein, glyceraldehyde 3-phosphate dehydrogenase, hyaluronidase, streptokinase, streptolysin O and streptolysin S, amongst others (Reissmann et al, 2012;Sunaoshi et al, 2010;Suzuki et al, 2011;Watanabe et al, 2013). Consequently, human infections related to SDSE resemble those associated with group A streptococci .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…equisimilis (SDSE) has increasingly been recognized as the aetiological agent of several human invasive infections worldwide (Bruun et al, 2013;Sunaoshi et al, 2010;Takahashi et al, 2010Takahashi et al, , 2011Tsai et al, 2014). SDSE isolates are frequently classified as Lancefield group C or G. Comparative genomic analyses revealed that several commonly found group A streptococci virulence factors have also been detected in SDSE isolates, including C5a peptidase, M protein, glyceraldehyde 3-phosphate dehydrogenase, hyaluronidase, streptokinase, streptolysin O and streptolysin S, amongst others (Reissmann et al, 2012;Sunaoshi et al, 2010;Suzuki et al, 2011;Watanabe et al, 2013). Consequently, human infections related to SDSE resemble those associated with group A streptococci .…”
mentioning
confidence: 99%
“…Similar to group A streptococci, SDSE has also been linked to post-infectious sequelae such as glomerulonephritis and rheumatic fever (Takahashi et al, 2011). Although SDSE isolates remain susceptible to penicillin, different studies have reported an increased prevalence of antimicrobial resistance to non-b-lactam agents clinically employed for streptococcal infections, including tetracycline, clindamycin and erythromycin (Kim & Uh, 2004;Rato et al, 2010;Sunaoshi et al, 2010;Takahashi et al, 2011).It is well known that SDSE isolates can also be associated with equine and other animal diseases, including strangles, Abbreviations: MLST, multilocus sequence typing; SpP, sporadic pattern; SDSE, Streptococcus dysgalactiae subsp. equisimilis; UPGMA, unweighted pair-group method using arithmetic averages.…”
mentioning
confidence: 99%
“…No hay casos documentados como el que presentamos de endocarditis por este patógeno. Con respecto al tratamiento, Streptococcus de los grupos C y G son sensibles a betalactámicos y la penicilina como en nuestro caso se considera el fármaco de elección 12 . La cefalosporinas de tercera generación son altamente activas y por tanto frecuentemente utilizadas.…”
Section: Discussionunclassified
“…En un estudio en Japón, se encontraron diferencias significativas en relación a la genotipificación emm, al comparar los agentes aislados de pacientes con enfermedad invasora (stG485, stG6792 y stG2078) versus no invasora 11 .…”
Section: Discussionunclassified